AFFECTION OF GLADIOLUS PLANTS WITH BEAN YELLOW MOSAIC VIRUS, CUCUMBER MOSAIC VIRUS AND TOBACCO RINGSPOT VIRUS IN SOME NORTHERN AND CENTRAL REGIONS OF UKRAINE - SOVINSKA, R.; DUNICH, A.; MISHCHENKO, L. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
Gladioli can be affected with 15 species of viruses, which cause significant economic losses to both floriculture and agriculture. The most prevalent and harmful for gladioli are Bean yellow mosaic virus (BYMV) and Cucumber mosaic virus (CMV), circulating on the territory of Ukraine on vegetable, legume and other crops, and also Tobacco ringspot virus (TRSV), which is included into the List of regulated pests of Ukraine and is the subject to strict control. The aim of the work was to conduct testing of gladiolus plants for the presence of viral infection symptoms and to test them for the affection with the most widespread and dangerous viruses, namely: BYMV, CMV, TRSV. Visual diagnostics, enzyme-linked immunosorbent assay in DAS-ELISA modification, transmission electron microscopy method and statistical data analysis were used in this research. The results of the studies showed absence of TRSV in all tested samples. For the first time in Ukraine, it has been established that gladioli are infected by Bean yellow mosaic virus. Its circulation on gladioli has been registered in Poltava, Kyiv and Sumy regions. Gladioli were also found to be affected by CMV or mixed infection of these pathogens. Gladioli infection by BYMV and CMV in Kyiv region is 88.2% and 93.8%, in Poltava – 69.2% and 55.5%, in Sumy – 66.6% and 0%, respectively. Typical symptoms on gladiolus plants caused by CMV and BYMV isolates are leaf chlorotic stripes and flower color break, less often – spotting on the leaves and plant stunting. It has been revealed that affection of gladioli by CMV and BYMV can be asymptomatic. The diversity, nature and course of viral infections in gladioli demonstrate the relevance of further research and their monitoring in Ukraine.